The Factors Influencing Perceived Ease of Use of E-Learning by Accounting Lecturer - Nujmatul Laily; Fenty Shintya Riadani (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2019)
This research aims at analyzing the influence of one’s anxiety in using computer (computer anxiety), age and gender on perceived ease of use of e-learning by accounting lecturers through their self-efficacy in using computer (computer self-efficacy). The population used in this research is all 34 lecturers at accounting department in X University and the sample is taken using saturated sampling technique since the number of respondents is limited. The data are collected by distributing questionnaire to lecturers.  The hypotheses are tested using path analysis test. The research results indicate that: (1) Computer anxiety has insignificant influence on perceived ease of use through computer self-efficacy. (2) Respondent’s age has insignificant influence on perceived ease of use through computer self-efficacy. (3) Respondent’s gender has insignificant influence on perceived ease of use through computer self-efficacy.